2021
DOI: 10.1590/2317-1782/20202020042
|View full text |Cite
|
Sign up to set email alerts
|

Escala para rastreio de dislexia do desenvolvimento: evidências de validade e fidedignidade

Abstract: Resumo Objetivo Investigar validade e fidedignidade de uma escala de rastreio para dislexia do desenvolvimento (DD) no ensino fundamental preenchida por professores. Método Avaliação empírica - 12 professores responderam a Escala de Leitura e Escrita (ELE) sobre 95 alunos de 3º ano do ensino fundamental, em dois momentos; os escolares realizaram testes de leitura e escrita (variáveis externas) para investigar a correlação entre a escala e o desempenho dos mesmos. Realizaram-se (1) análise fatorial, (2) avali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Word reading accuracy seemingly improved for controls and experimental group children; however, supplementary analyses indicated that such improvement was significant only for children who played GraphoGame. This corroborates existing studies that suggest that GG helps leverage word-level decoding skills [ 39 , 40 , 41 ] and improving associations between letters and sounds [ 40 , 43 ]. The differences between group means were not statistically significant, however.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Word reading accuracy seemingly improved for controls and experimental group children; however, supplementary analyses indicated that such improvement was significant only for children who played GraphoGame. This corroborates existing studies that suggest that GG helps leverage word-level decoding skills [ 39 , 40 , 41 ] and improving associations between letters and sounds [ 40 , 43 ]. The differences between group means were not statistically significant, however.…”
Section: Discussionsupporting
confidence: 90%
“…We asked teachers to provide their assessment of the students using a screener for reading difficulties and dyslexia developed in Brazil [ 39 ]. We created an online version of the questionnaire which was e submitted by the teachers via Google forms.…”
Section: Methodsmentioning
confidence: 99%
“…The Good Readers showed adequate reading speed for their age, and the DD showed reading performance well below the expected levels for their age (Saraiva et al, 2006). A more detailed description of the DD evaluations can be found elsewhere (Bassôa et al, 2021; Buchweitz, Costa, et al, 2019; Toazza et al, 2017). The scores for reading fluency were significantly different between the groups, as expected (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The Reading Clinic was a pro‐bono service for children aged 8–11 years who present persistent reading difficulties (Buchweitz, Costa, et al, 2019; Costa et al, 2016; Toazza et al, 2017). The Clinic was part of a larger behavioral, neuropsychological and brain imaging study of dyslexia (Bassôa et al, 2021; Buchweitz, Costa, et al, 2019; Costa et al, 2016; Toazza et al, 2017). The Clinic provided free services for diagnosis of DD for 9 years, during which time hundreds of children and families sought the multidisciplinary evaluation of reading for struggling readers, a service that is generally scarce and inaccessible outside private services, in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Teachers used the Children's Reading and Writing Screening Scale (CRWSS) to evaluate students' reading and writing skills (Bassôa et al, 2021). The CRWSS employs a 4-point Likert scale across 16 items to gauge the frequency of potential difficulties in acquiring reading and writing skills in the school setting.…”
Section: Reading and Writing Skillsmentioning
confidence: 99%